When Clients Throw Punches and Chairs: How Mediators Respond to Violence. Issue 4 (17th October 2016) - Raines, Susan S.; Choi, Yeju
Abstract : Much is known about screening family law mediation cases for potential violence, but little is known about violence that occurs within or immediately after mediation. In this article, we present the findings of a survey of U.S. mediators who reported their experiences of violence across a variety of mediation case types. These mediators described how and when violence arose and also reported the techniques and interventions that they used to de‐escalate tensions and to respond to violence. Our goal is to better equip mediators to prevent violence when possible, and to respond effectively if violence does arise in mediation.